Development of ready to serve (rts) beverage based on Coconut skim milk - Abrar, M.M.A.; Sathees, D.; Jayasundara, J.M.M.A.; Yalagama, L.L.W.C.; Pathiraja, P.M.H.D. (Faculty of Agriculture, Eastern University Sri Lanka, 2020)
Coconut milk has been used as an important aspect of numerous Asian foods. The current study was based upon the potential development of a beverage from coconut skim milk in the market because of growing health concerns. The objective of this study was to develop skim coconut milk beverage and comparison of its quality. The study was carried out at the Coconut Processing Research Division, Coconut Research Institute, Lunuwila, Sri Lanka using 4*4 factorial complete randomized experimental design with different treatments. Three different kind of treatments using different concentrations of preservative, stabilizer and flavouring agent vz Sodium Metabisulphate and Carboxy Methyl Cellulose (CMC) and one flavouring agent were used for the preparation of a ready-to-serve beverage Treatment (T3) - developed by using 1% CMC stabilizer, 0.035% preservatives & 0.5% of flavoring agents was selected for the successful formulation of ready to serve beverage. A major Nutrient constituent were observed as 1.01% of protein, 0.84% of fat, 18.70% of sugar and 79.25% of water in Treatment (T3). Treatment (T3) showed a minimal microbial count of fewer than 1.00*101 Colonies/g and Storage stability of the minimum 4 months at the room temperature of 30+2°C with minimal change in nutritional composition. Results indicate that Coconut skim milk could be utilized as a successful substitute for the production of ready to drink beverages.
Keywords: Beverage; Coconut Milk; Coconut Skim Milk; Food processing